THE EFFECTIVENESS OF SOLUTION FOCUSED CONCISE GROUP COUNSELING TO DEVELOP STUDENTS' ACADEMIC SELF-CONCEPT - Fitria Umami; Netrawati (Yayasan Citra Dharma Cindekia, 2021)
Self-concept is everything that is in a person, both positive and negative. The development of self-concept is certainly a manifestation of the positive self-concept that exists in humans, in which case the development of self-concept leads to the academic development of students. The approach used in the academic development of students is a group counseling approach that focuses on SFBC solutions. By using this approach group members are required to be more active in the process of counseling activities. This approach focuses more on the present and future of students, in the sense that it does not ignore the past but does not really look at the causes why these problems can occur. The group leader asks several open-ended questions so that members can explain the problems they are feeling. Focusing on the solution certainly does not question the cause, where in the case of the group leader it is more to help its members find solutions.